Study On Signature-Based Network Intrusion Detection System For High-Speed Network Using Network Processing Unit (NPU) - Salim, Robin (2007)
This thesis discusses IDS and signature-based NIDS. It presents detailed technical study of IDS and NIDS by introducing their background information, components and challenges.